Perilipin-related protein regulates lipid metabolism in C. elegans - Chughtai, Ahmed Ali; Kaššák, Filip; Kostrouchová, Markéta; Novotný, Jan Philipp; Krause, Michael W; Saudek, Vladimír; Kostrouch, Zdenek; Kostrouchová, Marta (PeerJ, 2015)
Perilipins are lipid droplet surface proteins that contribute to fat metabolism by controlling the access of lipids to lipolytic enzymes. Perilipins have been identified in organisms as diverse as metazoa, fungi, and amoebas but strikingly not in nematodes. Here we identify the protein encoded by the W01A8.1 gene in Caenorhabditis elegans as the closest homologue and likely orthologue of metazoan perilipin. We demonstrate that nematode W01A8.1 is a cytoplasmic protein residing on lipid droplets similarly as human perilipins 1 and 2. Downregulation or elimination of W01A8.1 affects the appearance of lipid droplets resulting in the formation of large lipid droplets localized around the dividing nucleus during the early zygotic divisions. Visualization of lipid containing structures by CARS microscopy in vivo showed that lipid-containing structures become gradually enlarged during oogenesis and relocate during the first zygotic division around the dividing nucleus. In mutant embryos, the lipid containing structures show defective intracellular distribution in subsequent embryonic divisions and become gradually smaller during further development. In contrast to embryos, lipid-containing structures in enterocytes and in epidermal cells of adult animals are smaller in mutants than in wild type animals. Our results demonstrate the existence of a perilipin-related regulation of fat metabolism in nematodes and provide new possibilities for functional studies of lipid metabolism.